Self-Objectification and Personal Values. An Exploratory Study - Rollero, Chiara; De Piccoli, Norma (Frontiers in Psychology, 2017)
Self-objectification occurs when individuals treat themselves as objects to be viewed and evaluated based upon appearance. Literature has largely elucidated links between self-objectification and damaging outcomes in both men and women. The purpose of the present study was to extend past research on the antecedents of self-objectification. We were interested in the role played by specific ideological components, i.e., higher order personal values (self-enhancement, conservation, self-transcendence, and openness to change), in influencing the degree to which individuals internalise the objectifying perspective of the Western cultural milieu, i.e. self-objectify. Undergraduate participants (N=371, 76.8% women) completed measures of self-objectification (i.e. body surveillance and body shame), and endorsement of higher order values. Regression analyses demonstrated that self-enhancement is linked to higher self-objectification in both men and women, whereas conservation is related only to women’s body surveillance. Self-transcendence seemed to act as a buffer against men’s body surveillance, whereas openness to change resulted as a buffer against women’s body surveillance. Implications are discusses.